A novel front-end amplifier for gain-less charge readout in high-pressure gas TPC. (1st September 2022) - Gao, C.; Feng, W.; Tian, X.; Sun, X.; Huang, G.; Qiao, Y.; Hu, Z.; Ye, Q.; Li, D.
Abstract: This paper presents a novel low-noise front-end amplifier manufactured in a standard 130 nm CMOS process. The front-end amplifier is part of an integrated sensor, with an array of which, forms a charge readout plane in a high-pressure gaseous Time Projection Chamber (TPC) for 0 νββ search. The novel front-end amplifier composed of a source-drain follower and a common-source amplifier is proposed. The potential of both the source and drain node of the input transistor follows its gate. Hence the effective input capacitance contributed by the input transistor is significantly reduced. A hexagon charge collection electrode with a diameter of 1 mm is connected to the input node of the front-end amplifier. The shielding technique is applied and the shielding metal is connected to the source or drain node of the input transistor. Therefore, the effective input capacitance contributed by the charge collection electrode is decreased. The extraction result shows that the input capacitance is decreased from the 4 pf down to 7.4 fF. A test chip has been designed and an equivalent noise charge of 33 e − is achieved from the simulations.